Chemopreventive effect of dayak onion [Eleutherine bulbosa, Mill. (Urb)] against 7,12-dimethylbenz [α] anthracene (DMBA)-induced breast cancer in rats: study on cancer antigen 15-3 (CA 15-3) - Efrem, Deo Gratias; Ilmiawan, Muhammad In'am; Pratiwi, Sari Eka (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Dayak onion [Eleutherine bulbosa, Mill. (Urb)] is herbal plant believed to have anticancer effects. It contains triterpenoids, flavonoids, anthraquinones, and naphthoquinones which have antioxidants and anticancer activities. This study aimed to investigate the effect of ethanolic extract of dayak onion bulb (EEDO) on serum cancer antigen 15-3 (CA 15-3) levels in rats induced with 7,12-dimethylbenz [a] anthracene (DMBA). Thirty female Sprague Dawley rats were randomly divided into six groups, namely Normal Group, Positive Control Group (tamoxifen), Negative Control Group (dimethyl sulfoxide/DMSO) 5%), Treatment Group I (EEDO 180 mg/kgBW), Treatment Group II (EEDO 360 mg/kgBW) and Treatment Group III (EEDO 720 mg/kgBW). All groups, except the normal group, were induced with DMBA 20 mg/kg body weight. Serum CA 15-3 levels were determined using enzyme-linked immunosorbent assay (ELISA) method. The results showed significantly lower (p< 0.05) CA 15-3 levels in the Treatment Groups compared to the Negative Control Group. The most significant reduction in serum CA 15-3 level was observed in the Treatment Group I receiving EEDO at a dose of 180 mg/kgBW. In conclusion, the EEDO possesses a chemopreventive effect on DMBA-induced breast cancer in rats.